An improved method for assessing the technical accuracy of optical tracking systems for orthopaedic surgical navigation. Issue 4 (3rd June 2021) - Herregodts, Stijn; Verhaeghe, Mathijs; De Coninck, Bert; Forward, Malcolm; Verstraete, Matthias A.; Victor, Jan; De Baets, Patrick
Abstract: Background: Optical tracking systems (OTSs) are essential components of many modern computer assisted orthopaedic surgery (CAOS) systems but patient movement is often neglected in the evaluation of the accuracy. The aim of this study was to develop a representative test to assess the accuracy of OTSs including patient movement and demonstrate the effect of pointer design and OTS choice. Method: A mobile phantom with dynamic reference base (DRB) attached was designed and constructed. The point registration trueness and precision were evaluated for measurements with both a static and moving phantom. Results: The trueness of the total target registration error (TTRE) was 1.4 to 2.7 times worse with a moving phantom compared to a static phantom. Conclusion: The accuracy of OTSs for CAOS applications should be evaluated by measurements with a moving phantom as the evaluation of the TTRE with a static frame significantly underestimates the measurement error.